Students’ errors analysis in solving mathematics problems viewed from various perspectives - Indah Suciati (12 Waiheru, 2023)
This research aims to provide an analytical description of students' errors in solving mathematical problems from the perspective of Newman, Kastolan, Watson, Hadar, and Polya errors and the factors influencing them. So, a Systematic Literature Review with the Prisma model was used in this research. Data was collected via Google Scholar and DOAJ in the 2017-2022 period in the accredited national journal Sinta totaling 366 articles. The Miles & Huberman model is used in research to analyze data by collecting, reducing, presenting, and drawing conclusions. The results of this research provide information regarding error analysis from the perspective of the Newman, Kastolan, Watson, Hadar, and Polya steps, as well as their indicators. Apart from that, the findings also provide information on external and internal factors that influence students' mistakes both through the learning process and related to personal character, mathematical abilities, and gender. Therefore, a teacher or educator needs to analyze the results of students' answers/work related to solving mathematical problems so that teachers can diagnose their students' strengths and weaknesses. The results of this diagnosis can be a reference for teachers to reflect on learning to choose the right learning model or method for mathematics material that suits the student's condition.